2011
DOI: 10.1002/cmdc.201100232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro Anticancer Activity of Ruthenium–Cymene Complexes with Cyclohexyl‐Functionalized Ethylenediamine‐N,N′‐diacetate‐Type Ligands

Abstract: Herein we describe the synthesis, characterization, and anticancer activity of novel p-cymeneruthenium(II) complexes containing methyl, ethyl, n-propyl, and n-butyl esters of (S,S)-ethylenediamine-N,N'-di-2-(3-cyclohexyl)propanoic acid. The results of IR, UV/Vis, ESIMS, (1)H, and (13)C NMR characterization reveal that ligand coordination occurs through nitrogen donor atoms of the ester ligands, with the organoruthenium moiety being kept in complex. These ruthenium(II) complexes are cytotoxic toward various can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(64 reference statements)
0
20
0
2
Order By: Relevance
“…The conductivity of the solution depends on the electrolyte type, but it depends on the solvent as well. From the observed conductivities and based on the literature data, 34 we concluded that both complexes are a 1:1 type of electrolytes.…”
Section: ■ Experimental Sectionmentioning
confidence: 92%
“…The conductivity of the solution depends on the electrolyte type, but it depends on the solvent as well. From the observed conductivities and based on the literature data, 34 we concluded that both complexes are a 1:1 type of electrolytes.…”
Section: ■ Experimental Sectionmentioning
confidence: 92%
“…11 Because the concentration of oxygen in tumor cells is low, the environment is more reductive than in normal tissue, favouring the active reduced form. 8,12 A real revolution in medicine occurred with the discovery of non-steroidal anti-inflammatory drugs (NSAIDs), which have been proven to be biologically active compounds. NSAIDs are one of the most commonly used classes of medication.…”
Section: Introductionmentioning
confidence: 99%
“…The n-butyl ester was more efficient in comparison to acid from the same group of ligands. [10,11] These results have motivated our group to investigate the potential of some of the R 2 eddp-type esters for tumour targeting with a simple and convenient radiotracer method. Ga) have an important role in nuclear medicine either as diagnostic or therapeutic radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 96%